Sandford Fleming and Universal Time - Creet, Mario (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 1990)
ABSTRACTIn 1884, consensus was reached to extend the system of time zones based on Greenwich that been adopted a year before in North America. The event has not been explained well in other accounts. This article shows how and why agreement came about; it was the result of efforts made by key individuals, among whom was Sandford Fleming, using professional and scientific organizations new to North America.